Evaluation of topical photodynamic therapy of mammary carcinoma with an experimental gel containing liposomal hydroxyl-aluminium phthalocyanine - Sutoris, Karol; Vetvicka, David; Horak, Ladislav; Benes, Jiri; Nekvasil, Milos; Jezek, Petr; Zadinova, Marie; Pouckova, Pavla (Anticancer research, 2012)
BACKGROUND: Photodynamic therapy (PDT) is a clinically-accepted approach for the therapy of many types of cancer. This study focused on the treatment of mammarian carcinoma by topical administration of hydroxyl-aluminium phthalocyanine (AlOH-PC), compared to a clinically-approved photosensitizer (Metvix, Galderma & PhotoCure ASA, Inc., Oslo, Norway). MATERIALS AND METHODS: MDA-MB 231 cells were subcutaneously injected into the right flank of athymic nude mice. Mice with grown tumours were used for in vivo efficacy studies. Different doses of liposomal AlOH-PC were applied to determine the most effective dose. In later studies, Metvix or our liposomal-AlOH-PC gel formula were used. Topical application of photosensitizers was followed by the PDT irradiation at 600-700 nm (635 nm peak). Tumour growth was measured three times weekly. RESULTS: Therapeutic studies revealed that AlOH-PC treatment led to complete tumour remission in 90% (9/10) of experimental animals, whereas usage of the commercially available Metvix only postponed the tumour growth. Moreover, usage of liposomal AlOH-PC shortened the time allowed between the application of the photosensitizer and light exposure: for Metvix, hours are usually needed, while the tested liposomal AlOH-PC showed remarkable outcomes after only 10 min. CONCLUSION: Liposomal AlOH-PC gel appears to be potentially suitable for PDT of mammarian carcinoma.
Keywords: Animals; Indoles; nádory prsu; Organometallic Compounds; Female; indoly; Gels; Cell Line, Tumor; ženské pohlaví; Mice, Nude; Liposomes; lidé; organokovové sloučeniny; Photochemotherapy; Mice; komplexní sloučeniny; Breast Neoplasms; Photosensitizing Agents; liposomy; myši; fotosenzibilizující látky; Coordination Complexes; xenogenní modely - testy protinádorové aktivity; Adenocarcinoma; Male; gely; adenokarcinom; Xenograft Model Antitumor Assays; zvířata; mužské pohlaví; fotochemoterapie; myši nahé; nádorové buněčné linie; Humans